The Use Of Cassava Peel And Salt Fermementation Solution On The Shelf Life Of Red Tilla Filets At Low Temperature Storage Based On Organolpetic Characteristics - Evi Liviawaty; Auliyatul Hakim, Shally (Universitas Islam Lamongan, 2025)
One method to extend the shelf life of fish filets is through antibacterial preservation, which can be achieved using a cassava peel fermentation solution containing lactic acid bacteria that can combat spoilage bacteria in fish. This study aims to determine the effect of cassava peel fermentation solution on the organoleptic quality of red tilapia filets during low-temperature storage (5°-10°C). Red tilapia filets were soaked in a cassava peel fermentation solution with varying salt concentrations across four treatments: 0% (control), 2%, 3%, and 4%, with a soaking time of 30 minutes per filet according to the treatment. Observations were conducted on days 1, 4, 7, 8, 9, 10, 11, and 12, with organoleptic evaluations (appearance, aroma, slime, and texture) and data analysis using the Friedman statistical test, Multiple Comparison, and Bayes test. Results indicated that a 3% salt concentration yielded the best organoleptic value, especially on day 10, with aroma as the highest-ranked parameter according to the Bayes test (weight 0,44), followed by appearance (0,37), slime (0,10), and texture (0,08). Thus, cassava peel fermentation solution with a 3% salt concentration effectively extends the shelf life of red tilapia filets.